Implementation of a diabetes in pregnancy clinical register in a complex setting: Findings from a process evaluation. - Renae Kirkham; Cherie Whitbread; Christine Connors; Elizabeth Moore; Jacqueline A Boyle; Richa Richa; Federica Barzi; Shu Li; Michelle Dowden; Jeremy Oats; Chrissie Inglis; Margaret Cotter; et al. (PLoS ONE)
Background Rates of diabetes in pregnancy are disproportionately higher among Aboriginal than non-Aboriginal women in Australia. Additional challenges are posed by the context of Aboriginal health including remoteness and disadvantage. A clinical register was established in 2011 to improve care coordination, and as an epidemiological and quality assurance tool. This paper presents results from a process evaluation identifying what worked well, persisting challenges and opportunities for improvement. Methods Clinical register data were compared to the Northern Territory Midwives Data Collection. A cross-sectional survey of 113 health professionals across the region was also conducted in 2016 to assess use and value of the register; and five focus groups (49 healthcare professionals) documented improvements to models of care. Results From January 2012 to December 2015, 1,410 women were referred to the register, 48% of whom were Aboriginal. In 2014, women on the register represented 75% of those on the Midwives Data Collection for Aboriginal women with gestational diabetes and 100% for Aboriginal women with pre-existing diabetes. Since commencement of the register, an 80% increase in reported prevalence of gestational diabetes among Aboriginal women in the Midwives Data Collection occurred (2011-2013), prior to adoption of new diagnostic criteria (2014). As most women met both diagnostic criteria (81% in 2012 and 74% in 2015) it is unlikely that the changes in criteria contributed to this increase. Over half (57%) of survey respondents reported improvement in knowledge of the epidemiology of diabetes in pregnancy since establishment of the register. However, only 32% of survey respondents thought that the register improved care-coordination. The need for improved integration and awareness to increase use was also highlighted. Conclusion Although the register has not been reported to improve care coordination, it has contributed to increased reported prevalence of gestational diabetes among high risk Aboriginal women, in a routinely collected jurisdiction-wide pregnancy dataset. It has therefore contributed to an improved understanding of epidemiology and disease burden and may in future contribute to improved management and outcomes. Regions with similar challenges in context and high risk populations for diabetes in pregnancy may benefit from this experience of implementing a register.